Entropy-synergistic introduction as comprehensive research basis of complex objects state - Kozulia, T.V.; Kozulia, M.M. (Вопросы атомной науки и техники, 2020)
The article deals with information support formation problem for comprehensive state assessment definition of research various nature object as a result of establishing compliance with safety requirements. The factors state stabilization analysis methods system and stationary communication of the “environment – object” is proposed. On information-entropy changes assessment basis by results of cognitive analysis of graphological models of system objects, cause-effect relationships are established for the in uence manifestation between systems within object boundaries, external environment on object as a whole. Synergetics elements use for the essential mechanisms allocation in organizing order for selective instability and the regulation or arbitrary processes consolidation synchronization probabilistic manifestation in the interaction “environment – object” is proposed. Розглянута задача формування інформаційної підтримки визначення комплексної оцінки стану об’єкта дослідження різної природи як результат встановлення відповідності вимогам безпеки. Запропонована система методів аналізу факторів стабілізації стану та стаціонарності зв’язку «навколишнє середовище – об’єкт». На основі інформаційно-ентропійного оцінювання змін за результатами когнітивного аналізу графологічних моделей системних об’єктів встановлюються причинно-наслідкові зв’язки прояву впливу між системами в межах об’єкта та впливу зовнішнього середовища на об’єкт в цілому. Запропоновано використання елементів синергетики для виділення суттєвих механізмів організації порядку для вибіркової нестійкости та регулювання чи акріплення довільних процесів імовірнісного прояву синхронізації у взаємодії «навколишнє середовище – об’єкт». Рассмотрена задача формирования информационной поддержки определения комплексной оценки состояния объекта исследования разной природы как результат установления состояния требованиям безопасности. Предложена система методов анализа факторов стабилизации состояния и стационарности связи «окружающая среда – объект». На основе информационно-энтропийного оценивания изменений по результатам когнитивного анализа графологических моделей системных объектов устанавливаются причинно-следственные связи проявления влияния между системами на границах объекта, и влияния внешней среды на объект в целом. Предложено использование элементов синергетики для выделения существенных механизмов организации порядка для выборочной нестойкости и регулирования или упрочнения произвольных процессов вероятностного проявления синхронизации во взаимодействии «окружающая среда – объект».